Conservative Approach of a Dentigerous Cyst - Farah Chouchene; Wassim Ben Ameur; Habib Hamdi; Maissa Bouenba; Fatma Masmoudi; Ahlem Baaziz; Fethi Maatouk; Hichem Ghedira (Case Reports in Dentistry)
Dentigerous cysts (DC) are the most common odontogenic cystic lesions of inflammatory origin occurring in children. These lesions can be treated by enucleation with or without related impacted teeth or marsupialization/decompression. The latter procedures have been used successfully for many years, but decompression is increasingly recommended in children because of its good outcomes and the preservation of the developing tooth. This conservative surgical technic allows simultaneously the normal eruption of the involved permanent teeth and the ossification of the bony defect. The present report describes an 8-year-old female patient with an inflammatory DC associated with an endodontically treated primary molar accidentally discovered on panoramic radiograph. Decompression of the cyst was performed, by means of a removable space maintainer acting as an acrylic obturator after removal of teeth 83 and 84. Ten months after the decompression procedure, a complete resolution and regression of the cystic lesion with full spontaneous eruption of the premolar were observed.